University, city and territory. The Magrone Barracks as a new Innovation Park - Loredana Ficarelli; Mariangela Turchiarulo; Valentina Vacca (Techne)
Universities not only play the role of social elevator but also stand as a development engine for the Territories hosting them, through synergies between institutions and businesses. The Innovation Park project at the former Magrone Barracks is an innovative example of management and rehabilitation of abandoned state-owned property for creating a fragment of Bari’s urban landscape by expressing common values in which the University, the City and extended territorial areas can recognise themselves. There is a need for a paradigm shift in the interpretation of the design of these facilities, which can become genuine integrated “urban factories”, Community Hubs capable of offering new spaces for the urban fabric, attracting talent and generating businesses.